Teologija o laikih - Arko, Alenka (Bogoslovni vestnik, 2024)
The purpose of the paper is to shed light on the contribution of Catholic theology of the last two centuries to the question of the laity in the Church. From a brief historical overview, it is clear that theology has focused mainly on three aspects: first, on sensus fidei fidelium, in which, according to New Testament revelation, every baptised person shares and was first highlighted by J. H. Newman, on the theology of tria munera received in baptism emphasised by Y. Congar in the years before the Council, and on the question of ministries and charisms in the Church, particularly characteristic of theology after the Second Vatican Council. Theological reflection on the laity has been accompanied since antiquity by a division of the Church, established by divine law, into ordained ministers and an unordained people, which however in no way justifies a division between the active role of the former (clerics) and the passive role of the latter (laity), and their subordinate position which we can observe in the Church almost in any period. The last Council sought to overcome this division by stressing that all the members of the Church are first included in the people of God in the power of baptism and that all have equal dignity whatever their role and ministry might be, but in truth it is necessary to acknowledge that, the distinction between the two categories in the life of the Church is far from being overcame, because neither canonical solutions nor theological reflection are capable to do that. It can be only a result of conversion, kenotic attitude of all the members of the Church and of authentic obedience to the Holy Spirit.
Keywords: Congar, Yves; ecclesiology; ekleziologija; laiki v Cerkvi; lay people in the Church; ministries in the Church; Newman, John Henry; sensus fidei fidelium; službe v Cerkvi; tria munera